Three-Level Meta-Analysis of Single-Case Data Regarding the Effects of Peer Tutoring on Academic and Social-Behavioral Outcomes for At-Risk Students and Students With Disabilities. (April 2021) - Moeyaert, Mariola; Klingbeil, David A.; Rodabaugh, Emily; Turan, Merve
Meta-analysis of single-case experimental designs may further knowledge about evidence-based practices for students needing remedial or special education. To contribute to evidence-based practice, a multivariate multilevel meta-analysis was used to synthesize the effectiveness of peer tutoring interventions on both academic and social-behavior outcomes. In total, 46 single-case studies met all inclusion criteria. Peer tutoring had a statistically significant effect on both academic and social-behavior outcomes, with a slightly larger effect on academic outcomes. Peer tutoring also had a significant effect on the trend in academic outcomes during the treatment phase (indicating that the intervention becomes more effective over time), but the effect on trends was slightly less than for social outcomes. Including moderators such as gender, age, disability type, and study quality reduced the amount of between-case and between-study heterogeneity. Limitations and implications of these findings are discussed.